2023
DOI: 10.3390/medicina59010165
|View full text |Cite
|
Sign up to set email alerts
|

Increased Thromboxane A2 Levels in Pulmonary Artery Smooth Muscle Cells Isolated from Patients with Chronic Obstructive Pulmonary Disease

Abstract: Introduction: Pulmonary hypertension due to chronic obstructive pulmonary disease (COPD) is classified as Group 3 pulmonary hypertension, with no current proven targeted therapies. It has been shown that cigarette smoke, the main risk factor for COPD, can increase thromboxane A2 production in healthy human pulmonary artery smooth muscle cells and pulmonary artery endothelial cells, and that blocking the effect of increased thromboxane A2 using daltroban, a thromboxane A2 receptor antagonist, can inhibit cigare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…We have previously demonstrated that TXA 2 is increased in human PASMCs isolated from smokers with COPD compared with TXA 2 levels in healthy PASMCs ( 145 ). More importantly, the balance between vasoconstrictive TXA 2 and vasoprotective PGI 2 is found to be important in the homeostasis of vascular function.…”
Section: Imbalanced Vasoactive Gene Expression and Mediator Release I...mentioning
confidence: 99%
“…We have previously demonstrated that TXA 2 is increased in human PASMCs isolated from smokers with COPD compared with TXA 2 levels in healthy PASMCs ( 145 ). More importantly, the balance between vasoconstrictive TXA 2 and vasoprotective PGI 2 is found to be important in the homeostasis of vascular function.…”
Section: Imbalanced Vasoactive Gene Expression and Mediator Release I...mentioning
confidence: 99%
“…Similar to ET-1, TxA2 has a role in maintaining hemostasis and pulmonary vascular tone in normal physiological conditions ( 39 ). On the other hand, unregulated TxA2 signaling, which is frequently linked to endothelial dysfunction and inflammation, can cause excessive vasoconstriction, platelet activation, and blood clotting incidents in the pulmonary circulation ( 40 , 41 ). In the pulmonary vascular system, ET-1 and TxA2 both essentially have vasoconstrictive actions, although their exact roles extend beyond simple vasoconstriction ( 40 ).…”
Section: Overview Of Pulmonary Vasculature and Its Functionmentioning
confidence: 99%
“…The underlying aetiology of COPD-associated pulmonary hypertension remains unclear; however, different pathways (prostaglandin I 2 , nitic oxide and endothelin) are thought to be involved. Among these pathways, we have previously shown that altered prostanoids (including prostaglandin I 2 ) pathways may play a pivotal role in pulmonary artery remodelling in cigarette smoke-induced COPD ( 14 , 15 ), suggesting that prostanoids pathways may serve as a potential therapeutic target for pulmonary hypertension due to COPD.…”
Section: Introductionmentioning
confidence: 99%